Removing Compliance: Interpersonal and Social Factors Affecting Insight Assessments - Curk, Polona; Gurbai, Sándor; Freyenhagen, Fabian (Frontiers in Psychiatry, 2020)
This paper probes the format and underlying assumptions of insight conceptualisations and assessment procedures in psychiatry. It does so with reference to the often-neglected perspective of the assessed person. It delineates what the mental steps involved in an insight assessment are for the assessed person, and how they become affected by the context and dynamics of the clinical setting. The paper examines how expectations of compliance in insight assessment tools and procedures extend far beyond treatment adherence, to compliance with diagnostic language and the assessment relationship. Such compliance can be ethically problematic and not in line with human rights standards, notably the Convention on the Rights of Persons with Disabilities. Most importantly, it can be counterproductive in supporting an individual to gain better insight in the sense of self-knowledge. The paper concludes with guidelines for a new approach to insight. This new approach requires taking into account currently neglected components of insight, in particular its relational and social dimensions, through which a person’s insight operates and develops, and through which it could be supported. Concretely, this would mean removing the condition of compliance and reflecting on the influence of the clinician-patient relationship and assessment situation on insight.